A revision of the Neotropical eumenine wasp genus Stenosigma Giordani Soika, 1978 (Hymenoptera, Vespidae) - Ferreira, Wellington D.; Oliveira, Letícia A. De; Hermes, Marcel G. (Zootaxa, 2018)
The Neotropical eumenine wasp genus Stenosigma Giordani Soika, 1978 is revised. Stenosigma mariae Ferreira & Hermes sp. nov. and S. panamensis Ferreira & Hermes sp. nov. are proposed as new. An updated identification key for species, new distributional records, and additional information on the species currently recognized within the genus are presented.